Molecular investigation on the impact of the pneumococcal polysaccharide-protein conjugates vaccine (PCV) on bacterial nasopharyngeal colonization in children - Olwagen, Courtney Paige (My University, 2017)
Background: Nasopharyngeal colonisation is a pre-requisite for developing bacterial respiratory and invasive disease. Immunisation of children with the pneumococcal conjugate vaccine (PCV) impacts upon colonising pneumococcal serotypes, which in turn could also affect the biome of the nasopharynx in relation to colonisation by other bacteria. Due to limitations in standard culture methods, the association between PCV-immunisation and bacterial carriage density is still unclear, including among HIV-infected children. In this study we aimed to evaluate the effect of infant vaccination with the 7-valent PCV (PCV7) on vaccine-serogroup colonisation in order to determine whether the increase in non-vaccine serotype (NVT) colonisation was due to unmasking of previously low density colonising serotypes or increase in acquisition of NVT. Also, we evaluated the association between PCV7 immunisation and HIV-infection on the prevalence density of nasopharyngeal colonisation by other common potentially pathogenic bacteria. Methods: A multiplex real-time qPCR assay was set up to detect 44 common pneumococcal serotypes and 5 bacterial pathogens including Streptococcus pneumoniae, Haemophilus influenzae, Moraxella catarrhalis, Staphylococcus aureus and Streptococcus pyogenes. All assays were optimised according to MIQE guidelines and their ability to detect multiple pneumococcal serotype/group and bacteria in archived nasopharyngeal swabs were evaluated. The multiplex qPCR assays were then used to evaluate vaccine-serotype, non-vaccine serotype and bacterial nasopharyngeal colonisation in achieved swabs of PCV7-vaccinated (at 6, 10 and 14 weeks of age) and PCV-unvaccinated African children at 9 and 15-16 months of age, prior to routine vaccination of children with PCV through the public immunisation program. In order to address the limitations of the qPCR assays, a nanofluidic real-time PCR assay was developed to simultaneously detect 53 pneumococcal serotypes, 6 serotypes of H. influenzae and 11 bacterial pathogens. Further, all assays were optimised and evaluated according to the MIQE guidelines and findings from Fluidigm and traditional qPCR assays were compared. Lastly, Fluidigm was used to evaluate the association of HIV-infection on the prevalence and density of nasopharyngeal colonisation at 9 and 16 months of age by common, potentially pathogenic bacteria including PCV7 pneumococcal serotypes, non-PCV7 serotypes, Haemophilus influenzae, non-typable Haemophilus influenzae, Staphylococcus aureus, Moraxella catarrhalis, Streptococcus pyogenes, Neisseria meningitidis, Neisseria lactamica, Bordetella pertussis, Bordetella parapertusis, Bordetella bronchiseptica and Bordetella holmesii in achieved nasophartngeal swabs collected from PCV7-vacciniated HIV-infected and HIV-uninfected children. Results: Molecular qPCR was more sensitive than culture in detecting multiple concurrent colonising pneumococcal serotypes as well as other common nasopharyngeal colonisers, with the majority of additional isolates detected by qPCR having a low carriage density (<104 CFU/ml). Further, qPCR identified a lower prevalence of PCV7-serotype colonisation among PCV7-vaccinated compared to PCV-unvaccinated children at 9 and 16 months of age [adjusted Odds Ratio (aOR): 0.37; 95% CI; 0.19-0.7 and 0.41; 95% CI; 0.26-0.63, respectively]; and an increase in NVT-serotype [aOR: 1.88; 95% CI; 1.02-3.48 and 2.2; 95% CI; 1.18-4.1] colonisation respectively. The increase in NVT carriage among PCV7-vaccinees was driven by serotype 19A, which increased by 53.4% (p=0.021) and 70.7% (p<0.001) at 9 and 16 months of age respectively. Further, 19A had a higher density of colonisation in PCV7-vaccinated groups compared to PCV-unvaccinated groups and was more likely to be identified as a primary than non-primary isolate in PCV7-vaccinated children alone. PCV immunisation was also associated with an increased prevalence of H. influenzae at 9 months (55.8% vs. 66.3%, p<0.001) and 16 months (72% vs. 62%, p=0.017) of age, while a temporary increase in the carriage prevalence of S. aureus was found in PCV7-vaccinated (18.9%) compared to PCV-unvaccinated children (11.1%, aOR 2.1; 95% CI 1.0-1.4; p=0.049) at 9 months of age only. The density of pneumococcus (4.68 vs. 4.28 CFU/ml; p=0.007), H. influenzae (3.86 vs. 4.34 CFU/ml; p=0.008), M. catarrhalis (2.98 vs. 3.52 CFU/ml; p<0.001) and S. aureus (3.06 vs. 4.02 CFU/ml; p=0.02) were also higher among PCV7-vaccinated compared to PCV-unvaccinated children at 9 months age, although this difference diminished with increasing age. There was excellent concordance between the qPCR and Fluidigm for carriage prevalence and density of the majority of assays, with Fluidigm identifying an additional 7 pneumococcal serotypes and 11 bacterial species above those detected by qPCR. Further, discordant results between the two PCR methods were strongly associated with a low carriage density (<102 CFU/ml). Using molecular Fluidigm, a lower carriage prevalence of overall pneumococci (58.6% vs. 69.9%; p=0.02), non-vaccine serotypes (27.8% vs. 40%; p=0.047) and H. influenzae (64.2% vs. 42.3%; p=0.01) was identified in HIV-infected children compared to HIV-uninfected children who were immunised with PCV7 at 9 months of age. No difference in the carriage prevalence of overall pneumococci was however found at 16 months of age (p=0.20), although the carriage prevalence of non-vaccine serotypes (50.9% vs. 60.4%; p=0.049) and H. influenzae (56% vs. 73.4%; p=0.02) was lower in HIV-infected children at 16 months of age. In addition, the density of overall pneumococcus was found to be higher in HIV-infected children (4.81 vs. 4.44 CFU/ml; p=0.014), despite the lower carriage prevalence at 9 months of age, which was driven by a higher density of vaccine serotypes/serogroups (4.21 vs. 3.72 CFU/ml; p=0.04). By 16 months of age, there was no difference in density of pneumococcal colonisation between the HIV-infected and HIV-uninfected children (p=0.89). No difference in the density of H. influenzae was found between HIV-infected and HIV-uninfected infants at 9 months of age (p=0.08); however, by 16 months of age, HIV-uninfected children had a higher density of overall H. influenzae colonisation (4.95 vs. 4.32 CFU/ml; p<0.001), which was largely due to the higher carriage density of NThinf in HIV-uninfected children (5.0 vs. 4.23 CFU/ml; p<0.001). Conclusion: Molecular qPCR assays were shown to be a promising alternative to WHO recommended culture in that multiple pneumococcal serotypes and other bacterial pathogens could be simultaneously detected as well as the bacterial load of each colonising bacteria quantified. The mechanism behind the vaccine effect was shown to be a combination of both serotype replacement and unmasking; however, the reduction in PCV7-serotype colonisation impacted on colonisation prevalence and density of other bacterial species of the nasopharynx and the clinical relevance of this needs further exploration in relation to mucosal and invasive disease outcomes, as well as for higher valence vaccines. While the higher carriage density of overall pneumococcus in HIV-infected children, despite the lower carriage prevalence might explain the higher invasive disease burden in HIV-infected compared to HIV-uninfected children even in the era of antiretroviral therapy treatment and PCV immunisation, future studies are required to provide clarity. Nevertheless, the findings from this thesis highlight the importance of continued surveillance of the circulation of pneumococcal serotypes as well as other bacterial pathogens especially in a population with a high burden of HIV-1 infection.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg 2017.
Keywords: Heptavalent Pneumococcal Conjugate Vaccine; Nasopharynx; Streptococcus pneumoniae